2008
DOI: 10.1051/0004-6361:20066806
|View full text |Cite
|
Sign up to set email alerts
|

Observations of pulsars at 9 millimetres

Abstract: Aims. The behaviour of the pulsar spectrum at high radio frequencies can provide decisive information about the nature of the radio emission mechanism. Methods. We report recent observations of a selected sample of pulsars at λ = 9 mm (32 GHz) with the 100-m Effelsberg radio telescope. Results. Three pulsars, PSR B0144+59, PSR B0823+26, and PSR B2022+50, were detected for the first time at this frequency. We confirm the earlier flux density measurements for a sample of six pulsars, and we are able to place upp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 33 publications
0
47
0
Order By: Relevance
“…(4) provided the best fit with a nano-shot timescale of about 30 ps which is only 10% of what was found for typical pulsars by Löhmer et al (2008). Alternatives (3) and (5) gave slightly worse agreements with the data, but generally speaking one finds that these three functions match the data quite well within the measured frequency interval.…”
Section: J1852−0635mentioning
confidence: 75%
See 2 more Smart Citations
“…(4) provided the best fit with a nano-shot timescale of about 30 ps which is only 10% of what was found for typical pulsars by Löhmer et al (2008). Alternatives (3) and (5) gave slightly worse agreements with the data, but generally speaking one finds that these three functions match the data quite well within the measured frequency interval.…”
Section: J1852−0635mentioning
confidence: 75%
“…It seems to be obvious that we are dealing with a GPS-type spectrum. However, the object is a potential candidate for a pulsar with spectra described using the model presented in Löhmer et al (2008). Thus, we attempted to fit three different functions that had been proposed in the literature, where…”
Section: J1852−0635mentioning
confidence: 99%
See 1 more Smart Citation
“…There is no correlation between the profile type and the pulsar spectrum (M00). However, Löhmer et al (2008) show that the spectrum of PSR B0144+59 has a "turn up" at 5 GHz to 10 GHz, which may be caused by its peculiar high-frequency profile evolution. Lorimer et al (1995, hereafter L95) show a positive spectral index for some pulsars between 400 MHz and 1600 MHz.…”
Section: Introductionmentioning
confidence: 91%
“…and there are indications of regular patterns of narrow emission regions separated on scales of a few m in Crab high-frequency giant pulses (Jessner et al 2010). Loehmer et al (2008) have shown that the superposition of sub-nanosecond emissions can also provide an explanation for the observed form of pulsar spectra. Our described solutions are stationary, but highly sensitive to the value of 1−κ κ and we expect small variations of the current density to cause large fluctuations in the local radio emission.…”
mentioning
confidence: 99%